Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.1608151907011804.a01
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoric Acids and Phosphates

Abstract: Most commercial applications of phosphorus‐containing materials are based on phosphoric acids and the phosphates. Uses, other than as fertilizer, include applications in detergency, foods and food processing, dental materials, dentifrices, metal surface treatments, flame retardency, etc. Structures and properties of orthophosphoric acid and condensed phosphoric acids are presented. The manufacture of technical‐ and food‐grade phosphoric acids by thermal and wet acid purification processes, as well as some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Binary System. The vapor pressure data 29 for the phosphoric acid + water system at various temperatures were employed in regressing the electrolyte NRTL parameters, as tabulated in Table 3, for the pairs of H 3 PO 4 −H 2 O and H + [H 2 PO 4 ] − −H 2 O. The comparison between the literature data and correlation is illustrated in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary System. The vapor pressure data 29 for the phosphoric acid + water system at various temperatures were employed in regressing the electrolyte NRTL parameters, as tabulated in Table 3, for the pairs of H 3 PO 4 −H 2 O and H + [H 2 PO 4 ] − −H 2 O. The comparison between the literature data and correlation is illustrated in Figure 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Boiling point of phosphoric acid aqueous solution at 1 atm: ■, literature; ○, experiment; −, electrolyte NRTL model.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The general scheme to manufacture phosphate salts can be summarised as follows (Gard, 2006): orthophosphoric acid (H 3 PO 4 ) is allow to react with the appropriate bases (e.g. sodium hydroxide, aluminium hydroxide, ammonia) until neutralisation is reached, to yield a solution or slurry with an acid/base ratio according to the orthophosphate product desired.…”
Section: Manufacturing Processmentioning
confidence: 99%
“…Aluminium salts (sodium and potassium sulphate) have been evaluated by JECFA in 1978(JECFA, 1978 that concluded that the use of aluminium metal as a silvering decoration for certain items of confectionary was not considered to present a health hazard. SALP (E 541) was evaluated by JECFA in 1982, 1985, 1986, 1988, 2006(JECFA, 1982, 1986, 1987, 1989. In its first evaluation in 1982, a temporary acceptable daily intake (ADI) of 0-6 mg/kg body weight (bw) was allocated due to insufficient data.…”
Section: Information On Existing Authorisations and Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation